2021
DOI: 10.1007/s12024-021-00370-4
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variability in homicide rates following the COVID-19 pandemic

Abstract: It has been demonstrated in a number of communities that the rates of serious crimes such as homicides and intimate partner violence have increased as a result of lockdowns due to COVID-19. To ascertain whether this is a universal trend the electronic autopsy files at Forensic Science South Australia, Adelaide, Australia, were searched for all homicides occurring between January 2015 and December 2020. There were 92 cases with 17 homicides in 2015 out of a total of 1356 cases (1.3%),18 in 2016 (18/1340 = 1.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…We found minimal impact of the pandemic lockdown stages on homicides rates in Ontario, particularly when comparing to recent years. This contrasts with other reports that have documented homicide deaths to have increased 23 and decreased 10 , 24 and suggest reports of increased domestic violence rates in some jurisdictions following stay-at-home orders 1 may not translate into increased homicide rates in Ontario. Other studies have similarly found a consistent homicide rate in some regions.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…We found minimal impact of the pandemic lockdown stages on homicides rates in Ontario, particularly when comparing to recent years. This contrasts with other reports that have documented homicide deaths to have increased 23 and decreased 10 , 24 and suggest reports of increased domestic violence rates in some jurisdictions following stay-at-home orders 1 may not translate into increased homicide rates in Ontario. Other studies have similarly found a consistent homicide rate in some regions.…”
Section: Discussioncontrasting
confidence: 93%
“…Various countries and jurisdictions report differing trends when comparing pre-pandemic death data to during or post-lockdown death types. These include decreased, 4 - 10 increased, 7 - 9 , 11 - 13 and steady 8 , 13 - 22 suicide rates; as well as increased, 23 decreased, 10 , 24 and steady 21 - 23 homicide rates. Given the variation of the studies thus far, the indirect effects of the COVID-19 pandemic on the frequency of non-natural deaths are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although traditionally there is a correlation between domestic violence and homicide cases (Iratzoqui & McCutcheon, 2018), during the COVID-19 confinement measures, there was a reduction in homicide, especially in women (Byard, 2021; Calderon-Anyosa & Kaufman, 2020), despite the increase of intimate partner violence and domestic violence in general. This may be explained due to the fact that in general in most cases where the victim is a woman, their body is found in public places—where the access now is limited due to COVID-19 measures—rather than at home (Calderon-Anyosa & Kaufman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Certain types of IPA appear to have increased more than others, particularly psychological abuse (IPP) and remote forms of IPA (e.g., stalking and harassment) (e.g., Arenas-Arroyo et al, 2021;Lausi et al, 2021;McNeil et al, 2023;Soeiro et al, 2023;Trafford, 2022). However, the most severe form, IPH, did not increase in most countries and decreased in many (e.g., Aebi et al, 2021;Byard, 2021;Cantor et al, 2022;Miller et al, 2022).…”
Section: (How) Did Ipa Change During the Pandemic Period?mentioning
confidence: 99%